2023
DOI: 10.3390/life13051194
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes and Safety Profile of Trans-Foveal Subthreshold Micropulse Laser in Persistent Central Serous Chorioretinopathy

Abstract: Our study evaluated visual function changes after subthreshold micropulse laser (SML) treatment in persistent central serous chorioretinopathy (CSC) and SML safety profile. We conducted a prospective study including 31 fovea-involving CSC patients. The natural course was observed for the first 3 months, SML was performed at 3 months, and SML effectiveness was observed at 6 months. At all three clinical visits, optical coherence tomography (OCT), best corrected visual acuity (BCVA), contrast sensitivity (CS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…However, our study is the first to monitor pachyvessel diameter during MPLT treatment. Notably, the treatment was completely safe, as no damage to the RPE after the laser procedure was found at fundus autofluorescence (FAF), consistent with prior studies [4,9,12,13,[18][19][20].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…However, our study is the first to monitor pachyvessel diameter during MPLT treatment. Notably, the treatment was completely safe, as no damage to the RPE after the laser procedure was found at fundus autofluorescence (FAF), consistent with prior studies [4,9,12,13,[18][19][20].…”
Section: Discussionsupporting
confidence: 83%
“…However, in these cases, total SRF resolution was achieved only in 48.4% of CSC cases lasting three months [13]. The treatment significantly improved mean BCVA, especially in patients with a complete reduction of SRF, during the six-month follow-up period [12], [13]. After a two-year follow-up, we also found that the treatment was the most effective for patients suffering from acute CSC.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations